Diagnosis of primary headache in children younger than 6 years: A clinical challenge. (September 2017) - Torriero, Roberto; Capuano, Alessandro; Mariani, Rosanna; Frusciante, Roberto; Tarantino, Samuela; Papetti, Laura; Vigevano, Federico; Valeriani, Massimiliano
Background: Criteria defined by the International headache Society are commonly used for the diagnosis of the different headache types in both adults and children. However, some authors have stressed some limits of these criteria when applied to preschool age. Objective: Our study aimed to describe the characteristics of primary headaches in children younger than 6 years and investigate how often the International Classification of Headache Disorders (ICHD) criteria allow a definitive diagnosis. Methods: This retrospective study analysed the clinical feature of 368 children younger than 6 years with primary headache. Results: We found that in our patients the percentage of undefined diagnosis was high when either the ICHD-II or the ICHD-III criteria were used. More than 70% of our children showed a duration of their attacks shorter than 1 hour. The absence of photophobia/phonophobia and nausea/vomiting significantly correlate with tension-type headache (TTH) and probable TTH. The number of first-degree relatives with migraine was positively correlated to the diagnosis of migraine in the patients ( p  < 0.001). Conclusions: Our study showed that the ICHD-III criteria are difficult to use in children younger than 6 years. The problem is not solved by the reduction of the lowest duration limit for the diagnosis of migraine to 1 hour, as was done in the ICHD-II.